Analisa Alternatif Rencana Lokasi Pembangunan Panti Wreda Kota Blitar - Murtadho, Ahmad; Mufidah, Mufidah; Soaduon Panjaitan, Tigor Wilfritz (Jurnal Etnik: Ekonomi-Teknik, 2024)
Indonesia has now entered an era of an aging population structure. According to SUSENAS 2022, there are 10.48% of the population who are elderly. This is also the case in Blitar City. Blitar City currently does not have a nursing home, so it is necessary to determine a location that is planned for the future, because in the City Spatial Detail Plan (RDTR) of Blitar City 2017-2031 there is a plan to build a nursing home. However, the location listed in the RDTR is currently being used for other development, so alternative locations are needed that are suitable for the construction of a nursing home. The research method used was primary and secondary data. Primary data is data obtained from direct surveys at locations, while secondary data is data collection from literature studies such as journals, scientific articles, statutory regulations and so on.